Madness and civilization - "Foucault, Michel" (London, 2003)
In this classic account of madness, Michel Foucault shows once and for all why he is one of the most distinguished European philosophers since the end of World War II. Madness and Civilization, Foucault's first book and his finest accomplishment, will change the way in which you think about society. Evoking shock, pity and fascination, it might also make you question the way you think about yourself.
Keywords: Philosophy